2018
DOI: 10.1177/0043820018813474
|View full text |Cite
|
Sign up to set email alerts
|

The Paradox of Administrative Decentralization Reform in Young Asian Democracies:South Korea and Indonesia

Abstract: It is generally perceived that administrative decentralization reform in young democracies is a promise to improve democracy from below. Yet, in terms of democratic development, the impact of this process is ambivalent, and can be described as a paradox of reform. This article argues that preemptive countermeasures that offset problems predicted to emerge as the reform proceeds should be formulated as part of the reform through introducing a preventive policy paradigm in the area of democratic reform policy. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
0
5
0
1
Order By: Relevance
“…Pemerintah daerah memiliki otonomi yang luas dalam menjalankan urusan di daerah, termasuk dalam meningkatkan pelayanan umum sebagai dampak dari desentralisasi (Heo, 2018). Pemerintah daerah diakui sebagai pihak yang memberikan pelayanan langsung kepada masyarakat, termasuk pelayanan administratif, barang publik, dan jasa publik (Silalahi & Syafri, 2015).…”
Section: Pendahuluanunclassified
“…Pemerintah daerah memiliki otonomi yang luas dalam menjalankan urusan di daerah, termasuk dalam meningkatkan pelayanan umum sebagai dampak dari desentralisasi (Heo, 2018). Pemerintah daerah diakui sebagai pihak yang memberikan pelayanan langsung kepada masyarakat, termasuk pelayanan administratif, barang publik, dan jasa publik (Silalahi & Syafri, 2015).…”
Section: Pendahuluanunclassified
“…In other words, it can serve as a school of democracy for the common populace by enabling their participation in local development activities (Smith 1985;Wolman 1990;Paul 1987;Rietbergen-McCracken 1996;World Bank 1996;Shah 2006). Even so, it is not realised that many authoritarian regimes introduce decentralisation reforms merely to sustain the central government's inwardly exclusive governmentality, which means its methods of managing society and legitimising its authoritarian raison d'être by excluding individuals and groups which have the potential to oppose the will of the dictatorial government (Khan 2015;Heo 2018;Aslam 2019).…”
Section: Local Government and Barriers To Citizen Participationmentioning
confidence: 99%
“…In the context of Pakistan, however, Aslam (2019) found that dictators could use decentralisation reforms to create a new political support class among the local elites in order to legitimise the central military regime. Another purpose of such authoritarian regimes has been to prevent civil society from challenging them and thus ultimately gaining greater support and thereby sustaining their power by creating inwardly exclusive governmentality (Heo 2018). It is possible to see that there is a trend in other dictatorial regimes such as the People's Republic of China, the Democratic Republic of Congo and Rwanda, where decentralisation reforms are implemented in sham and cynical ways (Aslam 2019).…”
Section: Military and Bureaucratic Establishments And The Plight Of Public Participationmentioning
confidence: 99%
“…The capacity and capability of local governments show unsatisfactory results. Local governments often face several resource constraints, from human resources to infrastructure resources (Heo, 2018;Heywood & Harahap, 2009;Kristiansen & Santoso, 2006;Paramita, Yamazaki, Setiawati, & Koyama, 2018;Shoesmith, Franklin, & Hidayat, 2020). Implementation constraint makes the decentralisation management movement in Indonesia adjust.…”
Section: Capacity and Capability Variation Of Local Governmentmentioning
confidence: 99%